User preference between multimedia and printed materials for general reference at the Ateneo de Manila University Rizal Library - Ho, Dylan Joseph Anthony P. (2002)
This study used the survey and unobtrusive observation techniques in determining the user preference between multimedia and printed materials at the general reference section of the Ateneo de Manila University Rizal Library. It also identified the reasons for the users' preference, the strengths and weaknesses of the two forms of materials and elicit comments and recommendations of the patrons regarding the printed and multimedia materials of the section. There were 80 library users, equally divided between genders, who responded to the survey instrument. On the other hand, 40 users, 23 males and 17 females, were observed unobtrusively during the period of the study.